Dampak Implementasi Pembelajaran Abad 21 terhadap Motivasi Akademik Santri Pondok Pesantren al-Farros Tebuireng Jombang - Kholifah Nur Fitriyah; Jumari Jumari (AS-SABIQUN, 2026)
Entering the 21st century, Islamic education in Islamic boarding schools faces the challenge of shifting the learning paradigm from teacher-oriented to student-oriented in order to develop 4C competencies, namely collaboration, creativity, critical thinking, and communication, without eliminating the traditional identity of pesantren. The integration of the role-play method and the Wordwall digital platform has become an innovative strategy to transform classical diniyah learning into a more interactive process. This study aims to examine the effect of 21st-century learning on the academic motivation of students at Pondok Pesantren Al-Farros Tebuireng Jombang. This study used a quantitative approach with a causal associative design. The research population consisted of 66 students, with a sample of 32 students selected through purposive sampling. Data were collected using a Likert-scale questionnaire, and their validity and reliability were then tested using Pearson correlation and Cronbach’s Alpha. Hypothesis analysis was conducted using simple linear regression through the stages of normality, linearity, heteroscedasticity, and coefficient of determination tests. The results showed that 21st-century learning influenced students’ academic motivation by 38.4%. This finding confirms that the implementation of 21st-century learning through interactive methods and digital media can support the improvement of students’ academic motivation in the context of pesantren education. The implications of this study indicate the importance of Islamic boarding school educators’ willingness to explore the use of digital media as a more adaptive, participatory, and relevant learning alternative in response to the demands of 21st-century education.